Religions Viewpoints of Khalil Jubran (Khalil Gibran): A Critical Review - Aslani, Sardare; Amirian, Zahra (Al-Adab Journal, 2019)
Jubran Khalil Jubran was one of the thousands Lebanese youth who emigrated with his family to the United States because of inappropriate social, political and financial situations. Using his great potentialities, he became on of the most influential figures of the world in thinking, literary, and art dimensions. This study attempts to investigate 1)the influential and challenging character of Khalil Jubran in the Arab world, Europe, and America; 2) the challenging religious and literary viewpoints presented by Khalil Jubran; 3) his distinguished and unique viewpoints about ontology, religion, human, and society; 4) having freedom of religious expression with a specific and non-imitative style; 5) management and guidance of the Northern Mahjar academy; 6) great realization of humanistic and moral attitudes in his works; 7)deep contemplation in human mental and behavioral states and materializing them in different works of poetry, prose and essay; and 8)lack of religious and sectarian prejudice. Although he was born to a catholic family, his personality reflected Christianity thinking, Islam, and Buddhism; and great figures such as Jesus, Imam Ali, Buddha, Abolala Moeri, William Blake, William Wordsworth, Coleridge, Nietzsche, famous European and American novelist provided him with highly valuable experiences. A lot of his viewpoints are consistent with Islamic views. A few inconsistencies are, however, observed in relation to transpiration of the soul or transmogrification, a global single or common religion, contradiction between propagating religious unity and advocacy of legitimacy of multiplicity in thinking and morality; giving love to all humans even to the cruel and murderers! and frangibility and instability of religious beliefs because of integration of the origin of his thought, which will be investigated and criticized in this study.